Control Mass-Spring-Damper Based on Tuning Trade-off PID Controller - Adi Mulyadi; Muhammad Zainal Roisul Amin; Muhammad Khoirul Anam (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
This paper discusses control mass-spring-dumper (MSD) system used in vehicle suspensions. The vehicle suspension consists of mass, coil (spring), and shock absorber (dumper). MSD provided a shock effect when the vehicle was caused by the frictional force on the load. The dificulty to achive the stability of suspension and the following of set point tracking. Therefore, the proportional-integral-derivative (PID) based on tuning 1-degree of freedom (1-DOF) and 2-degree of freedom (2-DOF) were proposed to stability when the disturbance accours. The MSD equation was obtained by using the laplace transform and validated in Matlab Simulink. The result shows that the proposed PID control reduces disturbance rejection by the smaller set point tracking peak amplitude of 0.01, overshoot of 0.68%, rise time of 0.199 seconds. The 1-DOF tuning achieved set point tracking and disturbance rejection with a peak amplitude of 1.13, overshoot 12.9%, rise time 0.134 seconds, and the 2-DOF tuning achived set point tracking and disturbance rejection with peak amplitude of 1.07, overshoot 6.53%, rise time 1.28 seconds. The proposed PID control has the best performance than 1-DOF and 2-DOF controller.